Lewis acid-base integrated robust metal-organic framework and reconfigurable composite for solvent-free Biginelli condensation and tandem catalysis with size selectivity. (December 2022) - Seal, N.; Neogi, S.
Abstract: Aiming at environmentally benign catalyses with less energy consumption, reduction in chemical usage and minimization of wastes, metal-organic frameworks (MOFs) combining basic functionality enriched pores and unsaturated metal centers (UMCs) is most promising. Alternatively, astute tuning of channel dimension in these materials can benefit much anticipated size-exclusive catalysis, whereas fabrication of flexible MOF-composite is imperative considering facile applicability over real-life platforms. The pillar-bilayered and hydrolytically robust MOF, built from tri-carboxylate ligand, linear linker and solvent-bound [Cd3 (COO)6 ] secondary building unit exhibits N-functionality enriched porous channels and activation-driven generation of open metal sites. Benefiting from unique bifunctional character, the MOF acts as excellent solvent-free catalyst toward one-pot Biginelli reaction and deacetalization–Knoevenagel condensation under mild condition. Both the reactions transpire with broad substrate scope, high recyclability and superior activity to contemporary materials, wherein single-crystal X-ray diffraction is first time applied as product characterization tool. Judiciously designed control experiments validate individual catalytic routes, thereby substantiating the importance of contrasting pore-functionalities at the interface of structure–property synergism. To the best of three-component coupling and acid-base tandem catalysis, substrates with incompatible molecular dimension to that of the twofold interpenetration generated optimized pores exhibit insignificant conversion and demonstrate unprecedented pore-fitting-actuated size selectivity. In view of practically advanced and eco-friendly substrate design, reconfigurable MOF–cotton fiber composite is fabricated via in situ growth, which delivered excellent yields for both these reactions with comparable reusability to that of pristine framework, delineating a paradigm shift to smart, futuristic and green strategy in synergistic catalysis. Highlights: The chemo-robust metal-organic framework (MOF) exhibits unique combination of acid-base bifunctional pore character. Activated MOF unveils solvent-free, recyclable catalysis for tri-component Biginelli reaction with wide substrate scope. The MOF catalyses mild-condition tandem Knoevenagel condensation, where control experiments endorse mechanistic route. Poor conversion with large-sized substrates for both these reactions signifies pore-fitting induced size selectivity. In situ grown MOF-cotton fiber composite acts as dual-catalytic material with unaltered activity and recyclability.